Subset currents on surfaces - Sasaki, Dounnu (Memoirs of the American Mathematical Society, 2022)
Subset currents on hyperbolic groups were introduced by Kapovich and Nagnibeda as a generalization of geodesic currents on hyperbolic groups, which were introduced by Bonahon and have been successfully studied in the case of the fundamental group